Birds of a Feather Earn Together. Gender and Peer Effects at the Workplace - Julián Messina; Anna Sanz-de-Galdeano; Anastasia Terskaya (Institute of Labor Economics (IZA), 2024)
Utilizing comprehensive administrative data from Brazil, we investigate the impact of peer effects on wages, considering both within-gender and cross-gender dynamics. Since the average productivity of both individuals and their peers is unobservable, we estimate these values using worker fixed effects while accounting for occupational and firm sorting. Our findings reveal that within-gender peer effects have approximately twice the influence of cross-gender peer effects on wages for both males and females. Furthermore, we observe a reduction in the disparity between these two types of peer effects in settings characterized by greater gender equality.
Keywords: J16; J24; J31; M12; M54; 330; peer effects; gender; matched employer-employee data; identity; wage determination